Engineering geology for the New Millennium: Stick with the basics - HameJ, James V.; Adams, William R. (Journal of Nepal Geological Society, 2000)
Our experience indicates most problems and difficulties in geotechnical practice result from failure to apply available information, existing knowledge, and well-established project development procedures. Many, if not most, of these problems and difficulties result from failure to apply in an organised manner basic concepts and techniques of engineering geology. Future challenges and opportunities are outlined with emphasis on infrastructure projects in both developed and developing countries. Ten previously presented Fundamentals of Geotechnical Engineering Practice (geology, geometry, geomechanics, observation, imagination, common sense, precedents/experience, construction/constructability, communication, diplomacy) are updated and five new Fundamentals (history. field emphasis, checking, redundancy, flexibility) are added. All fifteen Fundamentals are focused on an observational engineering geology approach for developing the geotechnical framework of sites and problems. For geotechnical practice in the twenty-first century, we have a simple message: Stick with the basics- traditional concepts and procedures including the fifteen Fundamentals.